Book Review: Mark Faulkner: A New Literary History of the Long Twelfth Century: Language and Literature between Old and Middle English. 2022. ISBN: 978-1-00-903184-4. - Skaffari, Janne (The Association for Computers and the Humanities, 2026)
This is a book review of A New Literary History of the Long Twelfth Century: Language and Literature between Old and Middle English, authored by Mark Faulkner and published by Cambridge University Press in 2022. Faulkner discusses texts written in English and the linguistic situation in England in the 150 years after the Norman Conquest of 1066.